Encore sur l’authenticité de l’Hexaéméron d’Anastase le Sinaïte - Zaganas, Dimitrios (2017)
The article re-examines the thorny question of the authenticity of Anastasius Sinaita’s Hexaemeron, which has been recently debated again by K.- H. Uthemann. A critical discussion of old and new arguments against the authenticity permits, on one hand, to reject the allegedly late dating and the inaccurate title appended to the Hexaemeron, and on the other hand, to express serious doubts about the cited theological differences between the Hexaemeron and the two Homilies on the making of man which are securely attributed to Anastasius. Moreover, a reassessment of the undeniable connection between the aforementioned texts provides strong evidence in support of the Anastasian authorship of the Hexaemeron.null
Keywords: Altertumswissenschaften; Byzantinistik; Diverses; Geschichte; Historische Epochen; Patristik; Theologie und Religion